The Problematic Application of Quantitative Approach in the Humanities and Social Science - benazouaou, omer (Journal of Social Sciences and Humanities, 2020)
Most scholars and researchers agree in epistemological contexts, as well as the history of science and methodology science, that the development of modern science is thanks to the epistemic connection to mathematics, where the scientific discourse has become a purely symbolic discourse, according to which all scientific issues and topics are translated into mere constants and mathematical variables, which enabled access to a kind of scientific accuracy and credibility, which settled with them many of the scientific problems that have remained for years stuck and stick to scientific thought. That scientific accuracy and credibility had profound and direct repercussions and effects on the rest of the sciences. Especially the late and newly independent from philosophy, and prompted it to reconsider the way it deals with its topics, specifically to the language that it employs in its analyzes and scientific discussions, this approach applies to the humanities and social sciences system that has become striving to involve coding and objectification or what is known as employing the quantitative approach in Its scientific discourse, in order to be more scientific and objective, and we in this particular article will try to surround what is known as the quantitative approach in the humanities and social sciences in terms of the beginnings of its formation in its space and then its gradual inclusion in its issues. Most of the studies and research in this latter a Purely direct and holistic tend to employ this approach in the tradition of scientific and clear to those sciences that have been successful in the use of mathematics as a language in scientific subjects. However, the exciting thing here is the true unconscious methodological and epistemological way of employing that approach, and indeed the risks and deadlock that result from that employment is not scientific, so it was necessary to call for a review of this situation, and to reconsider the method of its use and its application in the optimal way with which to achieve A kind of honesty and rationality in understanding and interpreting the human and social phenomenon, which means that its approach is an adequate scientific approach that pushes for its control and formulation in scientific theories